STUDI KASUS TENTANGDINAMIKA RESILIENSI REMAJA DENGAN KELUARGA BROKEN HOME - Nia Nurulita; Rita Kurnia Susilowati (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
This study aims to determine the dynamic picture of adolescent resilience with broken home families. This study uses qualitative research methods with a case study approach. The results showed that respondents showed resilience dynamics tend to be the same, namely the formation of resilience based on individual learning processes of the problems faced, the ability of individuals to evaluate every action taken and the spiritual aspect of getting closer to God so that making religious values as a guide to life . Meanwhile subjects who have an optimistic ability and self-efficacy that have not been good, this is due to the learning process of individuals to deal with problems that are still developing, individual fears about their experiences of broken home families cause the difficulty of individuals to have the ability of optimism and efficacy well, this causes adolescents tend to doubt their abilities, thinking that the problems they face will occur in the future.Keywords:Â Resilience; Youth; Broken Home Family